Back to the Future: Imaginaries of Africa on East Asian Screens. Issue 1 (1st June 2021) - Nardy, Deanna T.; Coates, Jennifer; Coates, Jamie
Abstract : The Africa we see on Japanese and Chinese screens generally bears little relation to the geographic region and its socio-political and historical concerns. Yet since the popular Tarzan films that swept the 1920s Japanese box office, an imagined Africa has played a significant role in film texts that explore East Asian identities and their implications for global futures in the context of natural and man-made disaster. From narrative blockbusters such as Japan's Tarzan to indie horror films such as World Apartment Horror, African bodies and places reflect forms of collectivity imagined as lost, past, or missing, as well as the unresolved issues that this loss may produce. In documentaries like Ryūichi Sakamoto: Coda, these pasts also present potential solutions for the impending disasters of the Anthropocene. In contemporary Chinese cinema, Africa also embodies both a 'lost past' and a potential future. In films such as Wolf Warrior II, an imagined African locale presents both threats and promises in a climate of tense geopolitical and biopolitical change where China, rather than 'the West', will provide solutions. The tropes utilised in this film borrow from stereotypical African-inspired imagery in their depiction of violent hordes of sick and starving people unimpeded by the rule of law, yet the bodies of idealised young Africans also represent new possibilities to come. In this way, a stereotyped Africa figures in East Asian cinema as a reflexive temporal fold for imagining both lost pasts and uncertain futures. Note: Romanised Japanese film titles have been marked JPN and Chinese film titles CHN.